PENGALAMAN PERAWAT DALAM MENERAPKAN TERAPI COMPLEMENTARY ALTERNATIVE MEDICINEPADA PASIEN STROKE DI SUMATERA BARAT - Elfira Husna; Setiawan -; Rosina Tarigana (Fakultas Keperawatan Universitas Andalas, 2012)
Complementary alternative medicine therapy is a medical practice group and health which is considered as part of conventional treatment. Many studies indicate the frequent use of complementary alternative therapy by patients affected by chronic illness. It is used by neurologic disorder patients like stroke, compared with non neurologic disorder like hypnosis, yoga, herbal therapy, and acupunture. In their service to stroke patients, nurses play their role in giving information and education concerning complementary alternative therapy. Indonesian nurses are beginning to use this method in their practices so that many of them participate in training about it. The objective of the research was to explore nurses’ experience in applying complementary alternative medicine in stroke patients in West Sumatera. The research used descriptive phenomenological approach with 14 nurses. The data werw gathered by conducting in-depth interviews, guided interview, and filed records and analyzed by using Collaizzimethode (1978) through seven stages. The study found there were seven themes as follows: increase capability take care of patients, assist cope patient complaint, nurse give information about therapy alternative to patients, nurses give therapy as standard, add finances and relations, feel happiness and satisfaction, and barrier applying alternative therapy. The themes in in this research were new themes in qualitative research related to nurses’ experience in applying complementary alternative therapy in stroke patients.